Change of mortality of patients with acute ischemic stroke before and after 2015 - Park, Sang-Won; Lee, Ji Young; Heo, Nam Hun; Han, James Jisu; Lee, Eun Chae; Hong, Dong-Yong; Lee, Dong-Hun; Lee, Byung Cheol; Lim, Young Wha; Kim, Gui Ok; Lee, Man Ryul; Oh, Jae Sang (Frontiers in Neurology, 2022)
Introduction: Advances in the diagnosis and management of acute ischemic stroke (AIS) and the increased use of mechanical thrombectomy (MT) have improved the quality of care and prognosis of AIS patients since 2015. We investigated the changing trends in mortality of AIS patients in Korea before and after 2015. Materials and methods: A retrospective cohort study was conducted using combined anonymized data from the Acute Stroke Assessment Registry of Korea and the Health Insurance Review & Assessment Service database. Ischemic stroke patients with precise onset time and initial National Institute of Health Stroke Scale records were included. Results: Patients receiving MT treatment increased from 256 (2.7%) pre-2015 to 1,037 (3.9%) post-2015 (p < 0.001). Overall mortality significantly decreased from pre-2015 to post-2015. In pre-2015, intravenous thrombolysis (IVT) administered within 2 h significantly reduced 3-month mortality when compared with non-IVT. While in post-2015, IVT administered within 2 h significantly reduced the 3-month, 1-year, 2-year, and 4-year mortality (p < 0.05). MT only reduced 1-year mortality pre-2015; however, MT significantly reduced the 3-month, 1-year, and 2-year mortality post-2015 (p < 0.05). Post-stroke antiplatelet and anticoagulant drugs significantly reduced the 3-month, 1-year, 2-year, and 4-year mortality post-2015. Discussion: Since 2015, faster IVT significantly reduced the short- and long-term mortality in AIS patients; MT reduced the 3-month, 1-year, and 2-year mortality. Post-stroke antithrombotic medication significantly lowered the 2- and 4-year mortality since 2015. Conclusions: Changing trends in AIS management since 2015 have improved the prognosis of AIS patients.